Analysis of Multi-Factor Inundation Vulnerability in Palu City Using GIS-Based Weighted Overlay - Lusyana Eka Wardani; Nurhilal Fauziah Ramlan; Aisyah Protonia Tanjung; Maisarah; Qanitatul Isra Qamal (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Inundation recurs annually in Palu City despite its relatively low annual rainfall of 657 to 870 mm/year. This condition indicates that physical land characteristics strongly influence inundation vulnerability. This study assesses inundation vulnerability across the administrative area of Palu City using an expert-based GIS weighted overlay method. Six variables were analyzed: rainfall, soil texture, slope gradient, land use, topography, and river buffer zones. The assigned weights were rainfall 15%, soil texture 10%, slope gradient 10%, land use 25%, topography 20%, and river buffer zones 20%. Data were obtained from BPBD, BMKG, DEMNAS/BIG, SRTM/USGS, and DPUPR Palu City, then processed using ArcGIS 10.8. The final vulnerability index was classified into five classes using the equal interval method. The results show that 4.47 km² (1.13%) is very low, 138.07 km² (34.95%) low, 136.25 km² (34.49%) moderate, 103.45 km² (26.19%) high, and 12.82 km² (3.25%) very high. High and very high zones are concentrated in East Palu, South Palu, and West Palu. Mitigation priorities include river buffer control, drainage revitalization, and riparian revegetation.